Penyuluhan Orang Tua Dan Bimbingan Belajar Anak Di Jakarta Barat - Wiyun Philipus Tangkin; Juniriang Zendrato (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
The lack of parental knowledge about discipline influences the role of parents in educating their children. Thus, it forms those who lack of discipline. It became the background of Community Service carried out in the form of parental counseling and tutoring for children in Wijaya Kusuma Village, West Jakarta. This counseling aimed to make parents reflect more on their role as the main educator in the lives of their children. The learning guidance that was carried out was motivated by the attitude of children who were passive and still afraid to express themselves both in written and orally. In the implementation of this study guide, children were directed to get to know more about who they are, their families, their dreams, and their hopes. Children were trained to be able to express and describe images of themselves, their families, hopes, and ideals in oral and written forms. The methods used in tutoring varied such as games, interactive teachings, group works, and independent assignments. The results of the observations during learning were that children looked better in terms of character, which was more disciplined and showed a cooperative attitude with their friends. From the results of evaluating the implementation of counseling, parents felt that this counseling was important and useful for them in educating their children at home.